Hypoxia-Induced Oxidative Stress Modulation with Physical Activity - Debevec, Tadej; Millet, Grégoire P.; Pialoux, Vincent (Frontiers in Physiology, 2017)
Increased oxidative stress, defined as an imbalance between prooxidants and antioxidants, resulting in molecular damage and disruption of redox signaling, is associated with numerous pathophysiological processes and known to exacerbate chronic diseases. Prolonged systemic hypoxia, induced either by exposure to terrestrial altitude or a reduction in ambient O2 availability is known to elicit oxidative stress and thereby alter redox balance in healthy humans. The redox balance modulation is also highly dependent on the level of physical activity. For example, both high-intensity exercise and inactivity, representing the two ends of the physical activity spectrum, are known to promote oxidative stress. Numerous to-date studies indicate that hypoxia and exercise can exert additive influence upon redox balance alterations. However, recent evidence suggests that moderate physical activity can attenuate altitude/hypoxia-induced oxidative stress during long-term hypoxic exposure. The purpose of this review is to summarize recent findings on hypoxia-related oxidative stress modulation by different activity levels during prolonged hypoxic exposures and examine the potential mechanisms underlying the observed redox balance changes. The paper also explores the applicability of moderate activity as a strategy for attenuating hypoxia-related oxidative stress. Moreover, the potential of such moderate intensity activities used to counteract inactivity-related oxidative stress, often encountered in pathological, elderly and obese populations is also discussed. Finally, future research directions for investigating interactive effects of altitude/hypoxia and exercise on oxidative stress are proposed.